The Challenges of Teaching Practice for Students Mastering Vocabulary in Blended Learning - Dyaz Galuh Irianto; Muhammad Sofian Hadi (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
The aim of this research is to find out the students' challenges in learning vocabulary and the effectiveness of teaching practice in students’ vocabulary mastery. This research used a qualitative research method with a descriptive qualitative research design. The data source in this research was taken by participants at SMP Islam Terpadu Assalaam, in class 9C, in the academic year 2022/2023. The researcher used checklist observation and semi-structured interviews to collect the data in this research. This research shows that students’ confidence and understanding are the main challenges of teaching practice for students in mastery of vocabulary in blended learning. Berfore using YouTube videos and Role-play activities, 3 of 6 students feel difficult and not interested to learn vocabulary. After using YouTube videos and Role-play activities, the result of the study shows that 5 of 6 participants need such interactive media. After learning vocabulary using YouTube videos and Role-play activities, 5 of the 6 participants are interesting to learn vocabulary. 5 of 6 participants feel Role-play and YouTube videos can help them to master vocabulary in pronouncing the words, building sentences and understanding how to use the words.